Use of Dissolved Glucose on Cultured Media on the Survival Rate, Growth Rate and Stress Resistance of Saline Tilapia Larvae (Oreochromis niloticus) - Imran, Muh. Ali; Maharani, Yuni; Marding, Hardiati; Dahlia, Andi; Karim, Muh. Yusri (Torani Journal of Fisheries and Marine Science, 2018)
Saline tilapia fish is a result of technology engineering technique that is tolerant with brackish waters and sea with salinity ≥ 20 ppt. The main problem in the development of saline tilapia is the availability of seeds because the resulting synthesis is still low. One effort to overcome the problem of low tilapia salinity this is by providing dissolved organic material such as glucose. Glucose plays an important role as a source of energy for animals including tilapia. The aim of this research is to determine the optimum dose of dissolved glucose to the survival and growth of salt tilapia larvae (Oreochromis niloticus). The research was conducted from March to May 2017 at Brackish Water Aquaculture (BPBAP) Takalar, South Sulawesi. The research container using 25 L plastic volume basin amounted to 15 pieces. The test animals used were 7-day saline tilapia larvae of 0.03 gram sized for 20 days. The glucose used is pure glucose in powder form. The study was designed using a complete randomized design consisting of 5 treatments and each having 3 replications. The five treatments are 0, 50, 100, 150, 200 ppm per day added to the once-daily research container that is the morning. The result of variance analysis showed that soluble glucose administration had significant effect (p <0.01) on the synthesis and growth rate of saline tilapia fish. The highest survival rates and growth rates were achieved at 100 ppm doses of 94.44% and 14.93% / day respectively, while the lowest at doses of 0 ppm were 74.81% and 11.85% / day respectively.Keywords: glucose, salin tilapia, survival, growth rate